2020
DOI: 10.1038/s41598-020-59633-9
|View full text |Cite
|
Sign up to set email alerts
|

Positive intergroup contact modulates fusiform gyrus activity to black and white faces

Abstract: In this study, we investigated the effect of intergroup contact on processing of own-and other-race faces using functional Magnetic Resonance Imaging (fMRI). Previous studies have shown a neural ownrace effect with greater BOLD response to own race compared to other race faces. In our study, white participants completed a social-categorization task and an individuation task while viewing the faces of both black and white strangers after having answered questions about their previous experiences with black peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…Hein and colleagues studied under controlled lab conditions the effects of negative reinforcement learning on intergroup empathy in the Swiss immigrant context and found that during the experimental session, a positive learning experience towards outgroup members resulted in enhanced neural empathic response towards representations of outgroup. Farmer and colleagues found that positive intergroup contact did not link with implicit bias on the Implicit Association Test (IAT), but was reflected by reduced neural intergroup bias; however, these results were correlational ( 21 ). Finally, Valencia and colleagues utilized an intervention training in the context of ex-combatants reintegration and found that the intervention triggered covert neurofunctional reorganization even when in the absence of overt behavioral improvements ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hein and colleagues studied under controlled lab conditions the effects of negative reinforcement learning on intergroup empathy in the Swiss immigrant context and found that during the experimental session, a positive learning experience towards outgroup members resulted in enhanced neural empathic response towards representations of outgroup. Farmer and colleagues found that positive intergroup contact did not link with implicit bias on the Implicit Association Test (IAT), but was reflected by reduced neural intergroup bias; however, these results were correlational ( 21 ). Finally, Valencia and colleagues utilized an intervention training in the context of ex-combatants reintegration and found that the intervention triggered covert neurofunctional reorganization even when in the absence of overt behavioral improvements ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the fMRI mapping, 40 volumes per condition (face and object) were available for statistical analysis in SPM12 (Wellcome Centre for Human Neuroimaging, United Kingdom). Parameters were mainly selected based on the suggested analysis pipeline for the high-level visual cortex (Weiner and Grill-Spector, 2013) and previously used settings to obtain faces selective cortex regions on the ventral temporal cortex (Winston et al, 2004;Liu et al, 2008;Jonas et al, 2015;Schwarz et al, 2019;Farmer et al, 2020).…”
Section: Mapping Procedures Fmrimentioning
confidence: 99%
“…Functional neuroimaging research has identified the amygdala as being involved in processing in-group and out-membership, as well as race (26,38,39). Our finding that greater maternal assimilation is associated with weaker amygdala-fusiform connectivity in offspring is intriguing as previous literature demonstrates an association between the fusiform and race-based processing in adults (40)(41)(42)(43)(44). Amygdala-fusiform connectivity also plays a role in ethnoracial processing of faces (39,41,45).…”
Section: Discussionmentioning
confidence: 49%
“…At three months old, infants are able to start discriminating between own race and other race faces as the “other-race effect” develops(46). As in adults(42), familiarity causes infants to prefer faces of their own race to faces of other races(47), but with greater exposure to other race faces, this preference is negated(48). Further, studies on young infants have shown that the postnatal environmental exposures to people of different ethnoracial groups and cultures affects infants perception of race(49).…”
Section: Discussionmentioning
confidence: 99%